Love Expression in the Lyrics of “Ah W Noss” By Nancy Ajram: A Riffaterrean Semiotic Analysis - Anis, Firliani; Haeruddin, Haeruddin; Agussalim, Andi; Fitriani, Fitriani; Walidin, Muhammad (Journal of Language and Literature Studies, 2026)
Interpreting expressions of love in Arabic song lyrics is important because such texts often convey complex emotional meanings through symbolic and indirect language. In the context of the increasing popularity of Arabic songs in Indonesia, understanding these meanings becomes essential, particularly in representing women’s emotional experiences. This study aims to analyze the expression of love in the lyrics of Ah W Noss performed by Nancy Ajram using the semiotic approach of Michael Riffaterre. This study employs a descriptive qualitative approach. The primary data consist of the lyrics of Ah W Noss, while secondary data include relevant academic literature. Data were collected through listening and note-taking techniques and analyzed using Riffaterre’s semiotic stages: identification of indirect expression, heuristic reading, hermeneutic reading, and the determination of matrix, model, and variants. The findings show that love in the song is expressed as a complex emotional experience involving patience, sacrifice, emotional protest, inner exhaustion, and resilience. These meanings are conveyed through figurative language such as metaphor, ambiguity, and hyperbole, reflecting the inner conflict and reflective awareness of the female lyrical subject. Love is therefore constructed not merely as a romantic feeling, but as a dynamic and critical emotional process shaped by imbalance and endurance. In conclusion, this study demonstrates that Michael Riffaterre’s semiotic approach is effective in uncovering layered meanings in song lyrics. The findings contribute to semiotic and literary studies, particularly in understanding emotional complexity and women’s representation in Arabic popular songs.